Wesen und Erscheinungsformen der Transhumance: Zur Diskussion um einen agrargeographischen Begriff - Hofmeister, Burkhard (ERDKUNDE, 1961)
In the introduction of this paper, transhumance is contrasted with both total nomadism as well as summer mountain pasture economy (Almwirtschaft). It differs from the former by the existence of a permanent settlement inhabited throughout the year and by the raising of crops including perennial ones, and from the latter by its reliance on pastures suitable for grazing only at certain seasons and by the fact that only alternation between pastures makes livestock farming possible at all. Subsequently the different types of transhumance are distinguished on the basis of the following criteria: location of the permanent homestead in relation to the seasonably utilised pasture grounds; direction of movement of herds and flocks in spring and autumn; incorporation of the mountain foothills into the system of pasture sequence; seasonal stall feeding of the animals; utilisation of two or more than two seasonal pasture grounds in the course of twelve months. On their basis the following types of transhumance are recognised: 1st normal; 2nd inverted; 3rd hibernal or tropical; 4th petite; 5th partial or mixed; 6th complex. After discussing some special cases, i. e. the so-called commercial and the horizontal transhumance, some points related to transhumance as a whole are examined, namely its relation to the level of civilisation of the peoples who practise it; its relationship to subsistence farming and farming for marketing; the formation of social groupings and communal herds and flocks; the length of migration routes, and the use of rail and motor transport in the seasonal movement of the animals. Finally, taking into account all the phenomena mentioned above in all their variations, the following comprehensive definition of transhumance is arrived at: Transhumance is a system of semi-nomadic livestock farming with migration or transport of the stock normally between two, occasionally between more, only seasonably usable pasture grounds, which differ in their location as regards altitude, climatic conditions and vegetation. Winter stall feeding may occur but results from cropping not climatic requirements. The permanent homestead, nearly always located at one of the seasonal pasture grounds, and the respective pasture grounds of the other season are not organically linked with each other.